Outcome of different cerclage methods in two cases of congenital cervical insufficiency: a case report - Thakur, Pushpawati; Majumdar, Sagarika; Chandrawanshi, Veena; Singh, Vinita; Rajbhar, Sarita; Trigunait, Pragati (International Journal of Research in Medical Sciences, 2021)
Cervical insufficiency (CI) or progressive shortening and thinning of cervix is a contributor to perinatal mortality through spontaneous mid-trimester miscarriages or early preterm birth. Congenital factors for cervical insufficiency are rarer than acquired factors. The lack of definitive criteria or methods is a challenge for diagnosis of such cases. Different cerclage methods and timely cerclage have shown to improve the outcome of pregnancy in patients with congenital cervical insufficiency (CCI). Here, we report two cases of CCI managed with different methods of cerclage culminating in successful pregnancy outcomes.